2016
DOI: 10.1186/s40497-016-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Women entrepreneurship: research review and future directions

Abstract: Studies on women entrepreneurship have witnessed a rapid growth over the past 30 years. The field is in an adolescence stage with a considerable number of journal articles, literature reviews and books being published on women entrepreneurs. The objective of this study is twofold. First is to examine the number of papers published on women entrepreneurship in 12 established entrepreneurship journals from 1900 to 2016. Second is to assess the growth of the field by specifically reviewing literature reviews publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
152
1
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(167 citation statements)
references
References 24 publications
1
152
1
13
Order By: Relevance
“…1976-ban Schwarts kiadta az első tudományos tanulmányt a női vállalkozói tevékenységről a Journal of Contemporary Business folyóiratban és az első politikai jelentést 1979-ben, melynek a "The bottom line: Unequal enterprise in America" címet adta (Yadav -Unni, 2016). Más kutatá-sok olyan nőket vizsgáltak, akik a férfiak által dominált iparágban tevékenykedtek.…”
Section: Női Vállalkozók a Kutatások Középpontjában -A Folyamat Leírásaunclassified
“…1976-ban Schwarts kiadta az első tudományos tanulmányt a női vállalkozói tevékenységről a Journal of Contemporary Business folyóiratban és az első politikai jelentést 1979-ben, melynek a "The bottom line: Unequal enterprise in America" címet adta (Yadav -Unni, 2016). Más kutatá-sok olyan nőket vizsgáltak, akik a férfiak által dominált iparágban tevékenykedtek.…”
Section: Női Vállalkozók a Kutatások Középpontjában -A Folyamat Leírásaunclassified
“…Girişimcilik konulu araştırmaların 1930'lü yıllarda çoğunlukla erkekler üzerinde gerçekleştirildiği (Yadav ve Unni, 2016, s. 7) görülse de; 1970'li yıllarda kadın girişimciliği konulu araştırmaların yoğun biçimde gerçekleştirildiğini ifade etmek mümkündür (Jenningsve Brush, s. 2013). 1970 yılında Boserup'un yayınladığı "ekonomik kalkınmada kadınların rolü" isimli çalışma kadın girişimciliği alanındaki ilk çalışma olarak kabul edilmektedir (Sallan Gül ve Altındal, 2016, s. 1365 Ardından 1976 yılında Schwarts'ın yayınladığı akademik çalışma ve 1979 yılında çıkardığı "Sonuç: Amerika'da eşit olmayan girişim" başlıklı resmi raporu oldukça önemli akademik çalışmalar arasındadır (Casson vd., 2007, s. 612).…”
Section: Kadın Girişimciliğiunclassified
“…Kadınların, bu sektörü seçmesi tesadüfi olmamakla birlikte, bazı sebepleri de bulunmaktadır. Bunlar; (Yadav ve Unni, 2016, s.7) aşağıdaki gibidir;…”
Section: Turizm Sektöründe Kadın Girişimciliğiunclassified
“…Women entrepreneurs are globally recognized as the key engine for economic development and innovation (Davis & Abdiyeva, 2012;Ascher, 2012;Noguera, Alvarez, & Urbano, 2013;De Vita, Mari, & Poggesi, 2014;Yadav & Unni, 2016). Acs (2006), who chaired the research committee of Global Entrepreneurship Monitor (GEM) for two years, found that entrepreneurship driven by unmatched or unexploited business opportunities has a positive and significant effect on economic growth (Acs, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature review has shown that women entrepreneurship research still has a long way to go. Scholars are calling for more research on this subject in emerging countries and the cross-country aspect (e.g., Minniti & Naudé, 2010;De Vita et al, 2014;Yadav & Unni, 2016;Elston & Weidinger, 2015). Studies have identified different factors that influence women's decision to go into entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%